Law Enforcement of Criminal Defamation Through Electronic Media - Putri, Septavela Gusti; Irianto, Echwan; Prihatin AN, Dodik (University of Jember, 2019)
Defamation through Electronic Media as regulated in Article 27 paragraph (3) of Law No. 19 of 2016 on amendments to Law No. 11 of 2008 on Information and Electronic Transactions does not explain in detail the elements of